Pengaruh Antara Kepuasan konsumen dengan Loyalitas Pada Konsumen Smartphone Samsung di PT. Nusa Abadi Sukses Arta - Kiki Afrylianty Rezwy; Hairul Anwar Dalimunthe (Universitas Medan Area, 2023)
This study aims to determine and analyze empirically the Effect of Consumer Satisfaction with Loyalty on Samsung Smartphone Consumers at PT. Nusa Abadi Success Arta. This study refers to quantitative methods with correlational analysis. The research sample was 45 people. The sampling technique in this study using incidental sampling is a sampling technique based on chance, that is, anyone who incidentally meets the researcher can be used as a sample. The customer satisfaction scale is based on aspects of customer satisfaction according to Manurung (2009): Expectations, Performance, Comparison, and Confirmation. Furthermore, loyalty is arranged based on aspects according to Fardani (2015) as follows: Repeat Purchase, namely loyalty to product purchases, Retention, namely resistance to negative influences regarding the company, Referalls, which refers to the total existence of the company. The two scales above use a Likert scale with 4 answer choices. Based on the calculation results of product moment correlation analysis, it can be seen that there is a positive influence between consumer satisfaction and consumer loyalty. It is assumed that the higher the customer satisfaction, the higher the loyalty, on the other hand, the lower the customer satisfaction, the lower the loyalty. This result is evidenced by the correlation coefficient rxy = 0.990, with significant p = 0.000 0.05. This means that the proposed hypothesis is accepted. The determinant coefficient (r2) of the influence between the independent variable and the dependent variable is r2= 0.979. This shows that consumer satisfaction is distributed 97.90% of consumer loyalty.